ANALYSIS OF THE EFFECTIVENESS OF MEDIA AND COMMUNICATION CHANNELS OF THE NORTH SUMATRA TOURISM OFFICE IN PROMOTING THE "SUMUT TOURISM FESTIVAL 2024" EVENT FOR STUDENTS OF THE D-IV MICE STUDY PROGRAM AT THE MEDAN STATE POLYTECHNIC - Putri Sosanti Sembiring; Dyah Seruni Rizqiana; Dwianita Dwianita; An Nisa Dian Rahma; Blangi Intan Maharani (Journal Analytica Islamica, 2026)
This research aims to analyze the effectiveness of the media and communication channels used by the North Sumatra Tourism Office in promoting the 2024 North Sumatra Tourism Festival event to students in the Diploma IV MICE Study Program at the Medan State Polytechnic. A quantitative descriptive approach was used, with 170 MICE students selected through random sampling. Data collection was conducted through a questionnaire with four main indicators: ease of access to promotional media, effectiveness of digital media in attracting young audiences, consistency of information across platforms, and suitability of communication channels to audience characteristics. Data were analyzed through validity, reliability, and descriptive frequency analysis. The results showed that the effectiveness of the North Sumatra Tourism Office's media and communication channels was categorized as good, with an overall average score of 3.87. Digital media such as Instagram, TikTok, and YouTube were considered the most effective because they were able to reach students quickly, engagingly, and interactively. This study concludes that the effectiveness of tourism public communication is determined not only by the content of the message, but also by the suitability of the media and delivery method to the behavior and needs of the audience.